The Importance of Personal Shopperâ€™s Services to Support Consumer Mobility - Y Hapsari, Ayuningtyas; Haizam Mohd Saudi, Mohd; ., . (International Journal of Engineering and Technology, 2018)
The demand for personal shopper is very high. A personal shopper becomes a new profession that is in great demand, especially for women, they can be personal shopper only with high trust capital. This study aims to determine the effect of service quality on purchasing decisions and the effect of pricing on purchasing decisions. And to find out how much influence the quality of services and pricing on purchasing decisions. This study used a descriptive verification method by distributing questionnaires to 115 consumers who never used personal shopper services and using accuracy level tests, feasibility tests for the Hosmer and Lemeshow models, the linear test for square r and the hypothesis test. Based on the results of calculations, it can be found that the quality of service has an influence on purchasing decisions and pricing has an influence on purchasing decisions.Â Â